2019
DOI: 10.1039/c9ra05113a
|View full text |Cite
|
Sign up to set email alerts
|

TiO2–Au composite nanofibers for photocatalytic hydrogen evolution

Abstract: The H2 production rate of TiO2–Au nanofibers is dramatically improved to 12 440 μmol g−1 h−1, 10 times that of pure TiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…It has been reported that new composite centres will be formed when the amount of the additive is excessive [11, 16, 19], which is not conducive to the separation of photogenerated electron–hole pairs. On the contrary, documents show that the more adding amount, the lower PL peak intensity [5, 8, 20]. In this study, 4% Ag rutile exhibits the lowest PL peak intensity suggesting that the higher concentration of Ag is beneficial to inhibit the recombination of photogenerated electrons and holes when the Ag/Ti molar ratio is no >4%.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…It has been reported that new composite centres will be formed when the amount of the additive is excessive [11, 16, 19], which is not conducive to the separation of photogenerated electron–hole pairs. On the contrary, documents show that the more adding amount, the lower PL peak intensity [5, 8, 20]. In this study, 4% Ag rutile exhibits the lowest PL peak intensity suggesting that the higher concentration of Ag is beneficial to inhibit the recombination of photogenerated electrons and holes when the Ag/Ti molar ratio is no >4%.…”
Section: Resultsmentioning
confidence: 57%
“…Therefore, the use of photocatalytic technology is a green and economical method and it has caused widespread concern [1][2][3]. Among many photocatalysts, titanium dioxide (TiO 2 ) has attracted the most attention due to its non-toxic, stable chemical property and high photocatalytic activity [4][5][6]. In practice, TiO 2 only absorbs ultraviolet light, which accounts for no >5% of sunlight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PL peak intensity decreases with the increase of the amount of noble metal element, which also has been reported in previous work. 47 Photocatalytic experiments show that high Ag concentration is not conducive to photocatalytic activity and 1% Ag–TiO 2 exhibits the highest decolorization rate. The decrease in photocatalytic performance of 2% Ag–TiO 2 and 4% Ag–TiO 2 should be attributed to the fact that Ag 0 particles are deposited on the surface of TiO 2 particles, and as the Ag concentration increases, excessive Ag particles will cover TiO 2 surface, reducing the utilization of light and reactive sites.…”
Section: Resultsmentioning
confidence: 99%
“…H, k, l indexes marked in Figure 6 were compared with Vanaja et al (2013) [ 48 ], Yang at al. (2019) [ 49 ], Reddy et al (2014) [ 50 ] and Sutrisno et al (2018) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%